D-limonene in the postharvest of ’THB’ papaya - Patrício, Flavia Figueira de Souza; Simon, Cátia Aparecida; Paradizo, Wilgner Fernandes; Sigismondi, Luciano Rastoldo; Pereira, Leandro Demetrio Becattini; Schmildt, Edilson Romais; Silva, Marcelo Barreto da; Kuhlcamp, Karin Tesch; Santana, Enilton Nascimento de; Dousseau-Arantes, Sara (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to verify if D-limonene in vitro presents inhibitory action on the mycelial growth of Colletotrichum spp. and antimicrobial activity against Enterococcus faecium and Escherichia coli, as well as to evaluate the effect of its concentrations on papaya disinfestation in the post-harvest process. For the in vitro tests, fungi were isolated from papaya fruit infected with anthracnose. For this, fruit fragments were disinfected and transferred to Petri dishes. Another test was carried out in vitro, to evaluate bactericidal activity, by for adding D-limonene to the suspension of the tested bacteria. Fruit physicochemical quality and disease incidence were evaluated. The application of D-limonene inhibited the mycelial growth of Colletotrichum spp. in vitro, with an increasing effect at increasing concentrations and a decreasing effect with time of product application. D-limonene was effective in inhibiting E. faecium and E. coli. There was no significant interaction between D-limonene rates and storage time for fruit quality or for disease incidence in ex vitro studies. D-limonene can be applied to papaya at postharvest, as it does not affect fruit quality and controls the growth of phytopathogens in vitro.